Pelagic food-webs in a changing Arctic: a trait-based perspective suggests a mode of resilience. (27th June 2018) - Renaud, Paul E; Daase, Malin; Banas, Neil S; Gabrielsen, Tove M; Søreide, Janne E; Varpe, Øystein; Cottier, Finlo; Falk-Petersen, Stig; Halsband, Claudia; Vogedes, Daniel; Heggland, Kristin; Berge, Jørgen; et al.
Abstract: Arctic marine ecosystems support fisheries of significant and increasing economic and nutritional value. Commercial stocks are sustained by pelagic food webs with relatively few keystone taxa mediating energy transfer to higher trophic levels, and it remains largely unknown how these taxa will be affected by changing climate and the influx of boreal taxa. Calanus species store large quantities of lipids, making these zooplankton a critical link in marine food-webs. The Arctic Calanus species are usually larger and, importantly, have been suggested to contain disproportionately larger lipid stores than their boreal congeners. Continued climate warming and subsequent changes in primary production regimes have been predicted to lead to a shift from the larger, lipid-rich Arctic species, Calanus glacialis and Calanus hyperboreus, toward the smaller, boreal Calanus finmarchicus in the European Arctic, with negative consequences for top predators. Our data show that lipid content is closely related to body size for all three species, i.e. is not a species-specific trait, and that there is considerable overlap in size between C. finmarchicus and C. glacialis . A trait-based life-history model was used to examine an idealized scenario where, in a changed Arctic with a longer period of primary production, C. glacialis - and C. hyperboreus -like copepods are indeed replaced by C. finmarchicus -like individuals, whether through competition, plasticity, hybridization, or evolution. However, the model finds that transfer of energy from primary producers to higher predators may actually be more efficient in this future scenario, because of the changes in generation length and population turnover rate that accompany the body-size shifts. These findings suggest that Arctic marine food webs may be more resilient to climate-related shifts in the Calanus complex than previously assumed.